When repetitive mental sets increase cognitive flexibility in adolescent obsessive–compulsive disorder. (30th March 2018) - Wolff, Nicole; Giller, Franziska; Buse, Judith; Roessner, Veit; Beste, Christian
Abstract : Background: A major facet of obsessive–compulsive disorder (OCD) is cognitive inflexibility. However, sometimes, cognitive flexibility can be needed to reuse recently abandoned mental sets. Therefore, cognitive flexibility can in certain cases be useful to reinstate some form of rigid, repetitive behavior characterizing OCD. We test the counterintuitive hypothesis that under such circumstances, cognitive flexibility is better in OCD patients than controls. Methods: We examined N  = 20 adolescent OCD patients and N  = 22 controls in a backward inhibition (BI) paradigm. This was combined with event‐related potential (ERP) recordings and source localization. The BI effect describes the cost of overcoming the inhibition of a recently abandoned mental set that is relevant again. Therefore, a strong BI effect is disadvantageous for cognitive flexibility. Results: Compared to controls, OCD patients revealed a smaller backward inhibition effect. The EEG data revealed larger P1 amplitudes in backward inhibition trials in the OCD group, which was due to activation differences in the inferior frontal gyrus (BA47). The severity of clinical symptoms predicted these neurophysiological modulations. The power of the observed effects was about 95%. Conclusions: The study shows that cognitive flexibility can be better in OCD than controls. This may be the case in situations where superior abilities in the reactivation of repeating mental sets and difficulties to process new ones coincide. This may be accomplished by intensified inhibitory control mechanisms. The results challenge the view on OCD, since OCD is not generally associated with cognitive inflexibility.